2011
DOI: 10.1103/physrevlett.107.175002
|View full text |Cite
|
Sign up to set email alerts
|

Coherent Control of High Harmonic Generation via Dual-Gas Multijet Arrays

Abstract: High harmonic generation (HHG) is a central driver of the rapidly growing field of ultrafast science. We present a novel quasiphase-matching (QPM) concept with a dual-gas multijet target leading, for the first time, to remarkable phase control between multiple HHG sources (>2) within the Rayleigh range. The alternating jet structure with driving and matching zones shows perfect coherent buildup for up to six QPM periods. Although not in the focus of the proof-of-principle studies presented here, we achieved co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
50
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(50 citation statements)
references
References 26 publications
0
50
0
Order By: Relevance
“…Recently, the generation of HH from multiple argon (Ar) gas jets separated by molecular hydrogen (H 2 ) "buffer" jets was shown to result in an enhancement of the HH yield by a factor of N 2 , where N is the number of Ar jets [10,11]. It was observed that by adjusting the backing pressure of the H 2 jets, quasi-phasematching could be achieved.…”
mentioning
confidence: 96%
See 3 more Smart Citations
“…Recently, the generation of HH from multiple argon (Ar) gas jets separated by molecular hydrogen (H 2 ) "buffer" jets was shown to result in an enhancement of the HH yield by a factor of N 2 , where N is the number of Ar jets [10,11]. It was observed that by adjusting the backing pressure of the H 2 jets, quasi-phasematching could be achieved.…”
mentioning
confidence: 96%
“…Instead, the H 2 acted as a passive plasma medium, with the gas pressure chosen such that the XUV pulses produced from subsequent Ar jets add constructively. However, previous work on multiphoton and tunneling ionization of atoms and molecules reveals that H 2 is in fact more difficult to ionize than Ar [12,13], which invalidates the proposed mechanism [10,11]. Here, we investigate HH generated from H 2 and Ar gases individually.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The characterization measurements of pulsed gas jets, gas puff targets, array of gas jets and dual-gas multi-jet targets proved to be useful in efficient generation of extreme ultraviolet (EUV) and soft X-ray (SXR) radiation [1,2] and was already reported in a variety of papers, [3][4][5][6][7][8][9][10], using different diagnostic methods. The most common method that was used in the characterization measurements of various target systems is laser interferometry [11,12].…”
Section: Introductionmentioning
confidence: 99%